Bis(3-phenylprop-2-enylidene)propane-1,3-diamine-kappa N-2,N' dibromidocobalt(II) - Montazerozohori, M.; Ali, Hapipah Mohd; Saharin, S.M.; Amirnasr, M.; Habibi, M.H. (International Union of Crystallography, 2009)
In the crystal structure of the title compound, [CoBr2(C21H22N2)], the Co-II atom is four-coordinated by two bromide anions and two N atoms from the bidentate Schiff base ligand in a distorted tetrahedral geometry.